(untitled) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2023)
Through the rapid increase in digital data, the use of tabular formats for data has also increased notably. However, the reusability of data is still an issue due to the lack of transparency in the presentation of data in spreadsheets. In our work with the Concepticon, we sometimes encounter spreadsheets provided by researchers that contain information not transparent to an external audience. Therefore, I offer guidelines on how to format tables with data and provide five concrete recommendations.